2005
DOI: 10.1002/ijc.21547
|View full text |Cite
|
Sign up to set email alerts
|

The pro‐cell death Bcl‐2 family member, BNIP3, is localized to the nucleus of human glial cells: Implications for glioblastoma multiforme tumor cell survival under hypoxia

Abstract: The Bcl-2 nineteen kilodalton interacting protein 3 (BNIP3) is a hypoxia-inducible proapoptotic member of the Bcl-2 family that induces cell death by associating with the mitochondria. Under normal conditions, BNIP3 is expressed in skeletal muscle and in the brain at low levels. In many human solid tumors, BNIP3 is upregulated in hypoxic regions but paradoxically, this BNIP3 expression fails to induce cell death. Herein, we have determined that BNIP3 is primarily localized to the nucleus of glial cells of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
113
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(132 citation statements)
references
References 24 publications
12
113
1
6
Order By: Relevance
“…Expression of the transmembrane domain deleted form of BNIP3 (BNIP3ΔTM) reduced the cyanide-induced cell death. BNIP3ΔTM functions as a dominant negative mutant to block integration of wildtype BNIP3 into the mitochondrial membrane [43]. In summary, it was shown that in cyanide-induced cell death, oxidative stress initiates upregulation of BNIP3 expression via a HIF-1α signaling regulated transcription.…”
Section: Discussionmentioning
confidence: 91%
“…Expression of the transmembrane domain deleted form of BNIP3 (BNIP3ΔTM) reduced the cyanide-induced cell death. BNIP3ΔTM functions as a dominant negative mutant to block integration of wildtype BNIP3 into the mitochondrial membrane [43]. In summary, it was shown that in cyanide-induced cell death, oxidative stress initiates upregulation of BNIP3 expression via a HIF-1α signaling regulated transcription.…”
Section: Discussionmentioning
confidence: 91%
“…More importantly, they also suggest that during ischemic stress, factors other than simple upregulation are important in generating the full apoptotic response to BNIP3 in ischemic injury. Whether this is hypoxia/acidosis-mediated post-translational modification and mitochondrial translocation of BNIP3 as has been suggested (Kubasiak et al, 2002;Kubli et al, 2008), or some other as-yet unidentified factor such as nuclear translocation that is seen in ischemic brain injury (Schmidt-Kastner et al, 2004;Burton et al, 2005), is not currently known.…”
Section: Transgenic Cardiac Overexpression Studies Of Bnip3 and Nix/bmentioning
confidence: 98%
“…There are multiple mechanisms that could control BNIP3 expression localization and function in tumors that are discussed below. The expression of BNIP3 is upregulated in primary prostate tumors, 56 glioblastoma multiforme (GBM) tumors, 57 endometrial cancer, 58 cervical tumors, 59 ductal carcinoma in situ (DCIS), 60 invasive breast carcinomas, 61 lung tumors, 62 ependymoma, 63 follicular lymphomas 64 and gastric adenocarcinomas. 65 (Table 1).…”
Section: Bnip3mentioning
confidence: 99%
“…BNIP3 is observed to be localized to the cytoplasm, the nucleus or the perinuclear space. BNIP3 is expressed in the nucleus in noncancerous primary human astrocyte cultures, normal brain sections 57 and chondrocytes of brachial cartilage, and also in the cytoplasm in the normal bronchial epithelium. 62 Expression in tumors has been observed to be exclusively nuclear, exclusively cytoplasmic or both nuclear and cytoplasmic.…”
Section: Bnip3mentioning
confidence: 99%
See 1 more Smart Citation